Imaging amyloid precursor protein in vivo: An axonal transport assay - Falzone, Tomas Luis (2012)
Fusion of fluorescent probes to axonally transported proteins represents an established approach that enables live imaging of axonal transport. In this approach, in vivo examination of fluorescent particle dynamics provides information about the length, directionality, and the velocity by which axonally transported proteins travel along axons. Analysis of these parameters provides information about the distribution of axonal proteins and their dynamics in and between different subcellular compartments. Establishing the movement behavior of amyloid precursor protein within axons indicated that live imaging approaches offer the opportunity to significantly enhance our understanding of the biology as well as pathology of axonal transport. This chapter provides a fluorescence-based procedure for measuring axonal transport of APP in cultured newborn mouse hippocampal neurons. © 2012 Springer Science+Business Media, LLC.